PENINGKATAN SARANA PRASARANA LINGKUNGAN TINGKAT KELURAHAN BACIRO PADA RPJM 2019-2023 - Jekson, Jekson; Jekson; Umar, Fahrul Roji; Airo, Diana; Anggytania, Hermina (MAJU : Indonesian Journal of Community Empowerment, 2024)
The Medium Term Development Plan (RPJM) for 2019-2023 for Baciro Village, Gondokusuman District is a planning document that aims to describe development directions and strategies for a five-year period in the region. This RPJM was prepared by involving the participation of the community, government and related stakeholders to achieve development that is sustainable, inclusive and competitive. This RPJM establishes the vision and mission of the Baciro Sub-District, which is to create a prosperous, independent and sustainable kelurahan, with a focus on improving the quality of life of the community, developing adequate infrastructure, developing the local economy, and equitable access to basic services. The main objectives of this RPJM are to improve people's welfare, create jobs, improve the quality of education, increase access to health, and strengthen good governance. This RPJM also identifies the resources needed to realize the development strategy, including human resources, funding, technology, and inter-agency cooperation. Monitoring and evaluation will be carried out periodically to ensure effective implementation and measure the achievement of predetermined development targets. Through the implementation of this RPJM, it is hoped that the Baciro Village can achieve sustainable growth, improve the quality of life of the community, and create a good and competitive environment. Active community participation, government support, and inter-agency collaboration will be the key to success in realizing the vision and mission of Baciro Village development in this medium-term period.